Could schizoaffective disorder, schizophrenia and bipolar I disorder be distinguishable using cognitive profiles?. (August 2018) - Chen, Chih-Ken; Lee, Chun-Yi; Lee, Yu; Hung, Chi-Fa; Huang, Yu-Chi; Lee, Sheng-Yu; Huang, Ming-Chyi; Chong, Mian-Yoon; Chen, Yi-Chih; Wang, Liang-Jen
Highlights: To determine whether the cognition profiles of patients with schizoaffective disorder (SAD), schizophrenia and bipolar disorder (BD) are distinguishable. Among the three patient groups, the schizophrenia group exhibited particularly impaired motor speed. The BD group performed best in attention, processing speed, executive function and the composite cognitive score. This accuracy rates of distinguishing SAD, schizophrenia and BD using cognitive differences were 38%, 47.9% and 46.3%. Abstract: This study seeks to determine whether the cognition profiles of patients with schizoaffective disorder (SAD), schizophrenia and bipolar I disorder (BD) are distinguishable. A total of 227 participants, comprising 88 healthy control subjects, 50 patients with SAD, 48 patients with schizophrenia and 41 patients with BD, were recruited. The participants' cognitive functions were evaluated using the Brief Assessment of Cognition in Schizophrenia (BACS). A discriminant functions analysis (DFA) was conducted to determine whether using cognitive performance can be used to distinguish these participant groups. Relative to healthy control subjects, patients with SAD, schizophrenia and BD exhibited significant deficits in all cognitive domains (verbal memory, working memory, motor speed, verbal fluency, attention and processing speed, executive function and a composite BACS score). Among the three patient groups, the schizophrenia group exhibited particularly impaired motor speed, and the BD group performed best in attention, processing speed, executive function and the composite BACS score. The classification accuracy rates of patients with SAD, schizophrenia and BD in the DFA model were 38%, 47.9% and 46.3%, respectively. These findings suggest that the impairments of some cognitive domains were less severe in patients with BD than in patients with schizophrenia or SAD.